Product-service systems in direct crop-livestock relationships. (19th May 2021) - Mamine, Fateh; Fares, M'hand
A major restructuring of the agricultural sector will soon occur that will result in a strong disconnect between stakeholders in the agricultural sector and the location of agricultural production and natural resource utilisation. Moreover, current issues related to economic and social-environmental aspects of agriculture justify the need to change the business model to one where sustainability is the main strategy of agricultural development. A new paradigm of the functionality-based economy - concretised by the product-service system (PSS) approach - has been built around the notion of consumption not being focused on goods, but rather on the services provided by goods. This article analyses seven case studies on the relationships between growers and breeders living in the same territory. It shows that these new organisational models are an interesting alternative that can change farming practices toward greater sustainability through the provision of services that aims to reduce environmental impact and improving eco-efficiency.